Reading and writing as “Cusp” provides the educational inclusion of a child with a neurodevelopmental disorders - Martínez, Mayluc (2018)
In this essay, it is made a reflection about reading and writing processes, and the practices which are part of school. In this regard, these processes are defined as cusp ( vertices), an adapted term from Applied Behavior Analysis (ABA), which is used for showing behaviors that have important consequences and with a more far-reaching for subsequent stages of child development (Rosales - Ruiz and Baer 1997) by virtue of appropriate from reading and writing, breaks through to the apprentice for several and new skills for being more connected with the environment, and at the same time, one more active participation within its school, familiar and social context. Learning will happen always if this is developed in the framework of some practices and contextualized appropriate activities considering as north, the quadruple valence of reading and writing which enables: learning more about the written language, more topics due to the written language, reducing or avoiding the existence of certain problematic behaviors, barriers which prevent a full participation of the individual in its environment and/or with its culture.